Skid dogs - Symington-Fedy, Emelia (Douglas & McIntyre, 2023)
"A raw and riveting coming-of-age story about the wild love of teenage friendships and the casual oppression of 1990s rape culture. Emelia Symington-Fedy grew up with her girl gang on the railroad tracks of a small town in British Columbia. Unsupervised and wild, the girls explored the power and shortcomings of "best" friendships and their growing sexuality. Two decades later an eighteen-year-old girl is murdered on Halloween on the same tracks, and Emelia returns to her hometown to stay with her mother, who is fearful of a murderer at large. While the media narrows its focus on how the girl dared be alone on the tracks, Symington-Fedy slowly comes to terms with the mistreatment of her own teenage body. Giving a bold and often darkly humorous first-hand account of nineties rape culture and the sexual coercion that still permeates girlhood, Symington-Fedy holds her hometown close and accountable and exposes the subtle ways that misogyny shows up daily. Award-winning poet and author Aislinn Hunter describes Skid Dogs as a "riveting, raucous and tender look at growing up a girl in a boy's world. [...] Beautifully written and bravely told, this book is the Stand By Me for girls that's been far too long in coming.""--